2023
DOI: 10.1021/acs.estlett.3c00080
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Mobile Colistin Resistance Genes within Los Angeles County Wastewater

Abstract: Wastewater surveillance of antibiotic resistance genes (ARGs) provides insight into the circulating antibiotic-resistant profile of its serviced population. Continual surveillance and characterization of wastewater ARGs could help identify emerging ARGs of clinical importance and their dissemination across bacterial species and locations. In this study, we detected four mobile colistin-resistant (mcr) gene variants (mcr-3.12, mcr-4.3, mcr-5.1, and mcr-9.1) in Los Angeles County wastewater between September 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
2
2
0
Order By: Relevance
“…Distinct seasonal mcr profiles were observed in air and liquid samples at each WWTP, with the most frequently identified gene variant being mcr -5, followed by mcr -8. The prevalence of mcr -5 across wastewater samples supports previous findings that observed high levels of this variant in hospital and municipal wastewater. , Interestingly, while mcr -8 was the second most abundant variant in this study, it has not previously been identified in municipal wastewater and is most often associated with aquatic environments. ,, …”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Distinct seasonal mcr profiles were observed in air and liquid samples at each WWTP, with the most frequently identified gene variant being mcr -5, followed by mcr -8. The prevalence of mcr -5 across wastewater samples supports previous findings that observed high levels of this variant in hospital and municipal wastewater. , Interestingly, while mcr -8 was the second most abundant variant in this study, it has not previously been identified in municipal wastewater and is most often associated with aquatic environments. ,, …”
Section: Resultssupporting
confidence: 89%
“…It is possible that the increased diversity of mcr variants observed in the low biomass air samples as compared to the high biomass liquid sludge samples may be due to differences in metagenomic coverage, and more gene diversity may be identified in the liquid samples with more extensive sequencing. However, even with this limitation, the results of this study support previous findings that observed a range of mcr variants in hospital and municipal wastewater. , ,, Additionally, this study is one of the first to examine seasonal patterns of mcr abundance and expands the understanding of environmental routes of mcr dissemination with the identification of mcr variants in WWTP bioaerosols.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Colistin resistance among multi-resistant Gram-negative bacteria from wastewater is undoubtedly in the upward trend considering the recent research reports and critical reviews. Recently, bacteria and associated genes that confer resistance to colistin were detected at the Los Angeles county's two largest wastewater plants, marking the first time traces of this particular antibiotic resistance in Los Angeles has been detected [12]. Mutations in chromosomal genes were primarily linked to colistin resistance initially.…”
mentioning
confidence: 99%